2013
DOI: 10.12669/pjms.301.3455
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and severity of low back pain in nurses working in intensive care units and influential factors

Abstract: Objective: The purpose of this research was to determine the frequency and severity of low back pain and influencing factors in nurses working in intensive care units. Methods: This research was conducted as a cross-sectional study with 114 nurses working in the intensive care units in the province of Gaziantep, Turkey. Study data were collected using a questionnaire form and visual analogue scale. Results: It was found that 84.2% of the nurses experienced low back pain, and 66.7% of the nurses evaluated this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
3
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 18 publications
10
43
3
11
Order By: Relevance
“…[9] It also differed from that of a study conducted among nurses working in Gaziantep, Turkey, as the prevalence of LBP in their study was estimated to be 84%. [12] Although other researchers [2,8,10,19] have suggested many causes and risk *Pediatrics, †obstetrics and gynecology, ‡internal medicine, §emergency medicine, **main theater and surgery † †intensive care unit (includes neonatal, pediatric and adult's ICUs), ‡oncology, ***body mass index (categories: Normal between 17 and 25, overweight between 25 and 30, obese more than 30). SMC: Salmaniya medical complex, ICU: Intensive care unit factors of LBP, not all of which were found to be significant in the studied population (e.g., Trauma history, frequent bending, frequent carrying of patients, and standing for long periods).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[9] It also differed from that of a study conducted among nurses working in Gaziantep, Turkey, as the prevalence of LBP in their study was estimated to be 84%. [12] Although other researchers [2,8,10,19] have suggested many causes and risk *Pediatrics, †obstetrics and gynecology, ‡internal medicine, §emergency medicine, **main theater and surgery † †intensive care unit (includes neonatal, pediatric and adult's ICUs), ‡oncology, ***body mass index (categories: Normal between 17 and 25, overweight between 25 and 30, obese more than 30). SMC: Salmaniya medical complex, ICU: Intensive care unit factors of LBP, not all of which were found to be significant in the studied population (e.g., Trauma history, frequent bending, frequent carrying of patients, and standing for long periods).…”
Section: Discussionmentioning
confidence: 99%
“…[11] In Gaziantep, Turkey, it was found that 84% of nurses experienced LBP. [12] Fewer studies were published from Gulf countries; however, in Saudi Arabia, LBP among nurses ranged between 48% and up to 85%. [6,13,14] In 2015, at Hamad General Hospital in Doha, a study was conducted on 254 nurses from different departments, and it concluded that the prevalence of LBP was high among them.…”
Section: International Journal Of Medical Science and Public Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Junke and Cho (21) showed that 90.3% of nurses in mean age 27.2 had back pain at least once a month (21.9% always, 40.7% once a week and 27.7% once a month). Also, Ovayolu et al (22) found that 84.2% of the nurses experienced LBP of which 66.7% evaluated this pain as 'a pain with moderate severity'. Moreover, Abedini et al (23) concluded that studied nurses believed that LBP had a negative influence on their job security and on their lives.…”
Section: Introductionmentioning
confidence: 99%
“…Supporting results have been found in another crosssectional study conducted in 2015 which found the intensity of low back pain to be 30.4% Mild, 34.8% Moderate and 34.8% having severe pain 12 . A similar study estimated severity of low back pain to be 26.0% mild, 66.7% moderate and 7.3% with severe or very severe intensity pain 13 . 53.7% of nurses with low back pain took medicines (prescribed or self-medication), 20.4% were relieved by physiotherapy while 25.9% were relieved by taking rest.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 82%